Humanity and the protection of the unborn : a jurisprudential rationale for the furtherance of the anthropological paradigm of international law - Myburgh, Georgia A. (University of the Free State, 2008)
This thesis is primarily concerned with the legal status of the unborn in international law. It investigates the lack of jurisprudence concerning the legal status of the unborn in this area of law and contends that such a lacuna is unacceptable. The unacceptability of this lack of discourse is highlighted in light of the concept of rationality; and rationality is presented as the best alternative method to deal with the legal status of the unborn, based on various justifications showing that the current method of legal discourse is not only devoid of rationality but inadequate to deal with this problem. Rational procedural and substantive attempts are then promoted to advance the legal status of the unborn in international law. Here the thesis emphasises the importance of taking into account requirements of humanity, sensitivity to animals and fairness, and continues to investigate the irrationality of abortion jurisprudence by arguing that the sole use of human rights and more specifically, the right to life and women’s rights, as determining the legal status of the unborn is part of the problem. Rationality requires an inclusive and sensitive approach and therefore, the sole use of concepts such as human rights, to the exclusion of science, anthropology, humanity and international justice, amongst others, are argued to be irrational. Scientific and anthropological consideration is also very important, not only to present an inclusive approach, but because these disciplines present us with some of the few convincing facts that can be used to aid philosophers when dealing with a topic where assumption and argument, rather than facts, are ample. However, this thesis does not pretend that a final or absolute solution on the legal status of the unborn is possible as cultural and ethical relativism as well as ideological affiliations present a problem to obtaining a universal rational outcome on the legal status of the unborn. However, it is stated that the possibility of a universal rational outcome, which represents an improvement on the contemporary situation, does exist and therefore, it would be irrational if such possibility were not attempted on rational grounds by way of procedure and substance, taking into account requirements of humanity.

Hierdie proefskrif is primêr gemoeid met die regstatus van die ongeborene in internasionale reg. Dit ondersoek die gebrek aan regsleer rakende die regstatus van die ongeborene in hierdie area van die reg en voer aan dat sodanige leemte onaanvaarbaar is. Die onaanvaarbaarheid van hierdie gebrek aan redevoering word na vore gebring in die lig van die konsep van rasionaliteit en hou laasgenoemde voor as die beste alternatiewe metode om met die regstatus van die ongeborene te handel, gebaseer op verskeie regverdigings wat toon dat die huidige metode van regsredevoering nie net aan rasionaliteit ontbreek nie, maar ook ontoereikend is om met hierdie probleem te handel. Rasionele prosessuele en wesenlike pogings word dan aangemoedig om die regstatus van die ongeborene in internasionale reg te bevorder. Hier beklemtoon die proefskrif die belangrikheid van die inagneming van die vereistes van menslikheid, sensitiwiteit jeens diere, asook regverdigheid en gaan die studie voort om die irrasionaliteit van aborsieregsleer te ondersoek deur te argumenteer dat die alleen gebruik van menseregte en meer spesifiek die reg tot lewe en vroueregte, as bepalend van die regstatus van die ongeborene, deel vorm van die probleem. Rasionaliteit vereis ’n inklusiewe en sensitiewe benadering en daarom word geredeneer dat die alleen gebruik van konsepte soos menseregte, tot die uitsluiting van onder andere die wetenskap, antropologie, mensheid en internasionale reg, irrasioneel is. Wetenskaplike en antropologiese oorweging is ook baie belangrik, nie net om ’n inklusiewe benadering voor te hou nie, maar omdat hierdie dissiplines ons van ’n paar oortuigende feite voorsien wat gebruik kan word om filosowe te help wanneer hulle met ’n onderwerp te doen het waar aanname en argument, eerder as feite, volop is. Hierdie proefskrif gee egter nie voor dat ’n finale of absolute oplossing oor die regstatus van die ongeborene moontlik is nie aangesien kulturele en etiese relativisme, asook ideologiese affiliasies, ’n probleem in die weg lê van die verkryging van ’n universele rasionele uitkoms oor die regstatus van die ongeborene. Dit word egter gestel dat die moontlikheid van ’n universele rasionele uitkoms, wat ’n verbetering op die kontemporêre situasie verteenwoordig, wel bestaan en daarom sal dit irrasioneel wees indien so ’n moontlikheid nie op rasionele gronde deur middel van prosedure en substansie, met inagneming van die vereistes van mensheid, oorweeg word nie.
Dissertation (LL.M. (Constitutional Law and Philisophy of Law))--University of the Free State, 2008
Keywords: Abortion; Unborn children (Law); Right to life; Reproductive rights; United Nations; Viability; Human rights; Foetus; Anthropology; Humanity; Reason; Rationality; International law